Nexus between commodities and banking sector financial soundness: The role of general macroeconomic setting in Ghana - Collins Baffour Kyei; Emmanuel Asafo-Adjei; Peterson Owusu Junior; Anokye Mohammed Adam; Anthony Adu-Asare Idun; Justice K.G Agyenim Boateng (Cogent Economics & Finance, 2023)
AbstractThe level of causation and interdependencies among three commodities (cocoa, gold, and Brent crude oil), five banking sector performance indicators (Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), Return on Equity (ROE), Return on Assets (ROA) and Core Liquid assets to total assets (CLATA)), and three general macroeconomic indicators (Inflation, Exchange rate and Global Economic Policy Uncertainty) are explored in this study. As a result, the wavelet techniques are employed to investigate time-frequency and frequency-dependent nexus in the Ghanaian context. In terms of time-frequency, a mix of negative and positive bi-causality among commodities, banking sector performance indicators, and macroeconomic indicators are found. Outcomes from the wavelet multipleprovide that these variables are highly integrated, with the exchange rate leading in the long-run. Hence, implying that exchange rate in Ghana has a high susceptibility to shocks before the other variables in the study. We advocate Government of Ghana and policy-makers should fine-tune policies that take into account the impact on other economic factors. Policies should be initiated to minimise fluctuations in the exchange rate. To limit the adverse impact of inflation and GEPU, it is required that effective and efficient country-level policies geared towards stability be initiated to resuscitate the economy.